EFFECTIVENESS OF MAJA FRUIT EXTRACT (Aegle marmelos) AS AN ALTERNATIVE FOR PEST CONTROL LIVING LOCKS (Locusta migratoria) - Wuarbanaran, Ona Adelci; Leiwakabessy, Fredy; Smith, Alwi (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: Control of wandering grasshoppers at the farmer level generally uses chemical insecticides which can damage non-target organisms, pest resistance, pest resurgence and cause residual effects Methods: Laboratory experimental research, although it can also be carried out outside the laboratory, its implementation applies laboratory principles. Results: The effectiveness of the mortality of maja fruit extract on wandering grasshoppers, in the treatment of giving 40% maja fruit extract, there was an increase in the number of deaths of wandering grasshoppers, where in the 10th minute there was 20% death, there had already been deaths compared to the treatment giving 20% extract with the same amount. wandering grasshoppers died by 100%. Conclusion: Maja fruit extract (Aegle marmelos), has the power to kill wandering grasshoppers (Locusta migratoria) because it contains tannins and saponins which are toxic and have a real effect in killing wandering grasshoppers